Legal Review of the Legal Position of the Private Sale and Purchase Agreement for Land Rights That Has Been Deeded (Case Study of Supreme Court Decision Number 08 K/Tun/2013) - Avisina, Muhammad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
The deed registration process is only recorded by a notary, not one that is made from the beginning by a notary. What if one party evades it? If the deed under hand has been deed deed by a notary, is the notary also responsible for the deed? In this study, the author discusses the legal status of the Sale and Purchase Agreement (PPJB) for land rights under hand that have been deed deed (Case Study Number 08 K/TUN/2013). The approach method used in this thesis is normative by using primary data as the main data by conducting, normative legal research is a process to find a rule of law, legal principles, or legal doctrines in order to answer the legal issues faced. In addition, there is also a special approach, namely the statutory approach (Statute Approach), the statutory approach as one of the research approaches used by the author by examining the laws and regulations related to the legal issues being studied. The position of Notary in Indonesia is very necessary, in the explanation section of the Notary Law (UUJN) it is stated about the importance of the existence of Notaries as made in Law No. 02 of 2014 concerning Amendments to Law No. 30 of 2004 concerning the Notary Position. Notary is defined as a public official who is authorized to make authentic deeds and other authorities as referred to in this Law or based on other laws. If we look at the other notary authorities as stated in Article 15 paragraph (2) letter b UUJN.Keywords: Agreement; Purchase; Sale; Warmerking.